Faktor- Faktor Yang Mempengaruhi Proses Pelaksanaan Pekerjaan Jalan Lingkar Kota Kendari II - Madu, La; Sunaryo, Sunaryo; Rachmat, Laoede Musa (Universitas Sulawesi Tenggara, 2020)
Project delays can come from service providers or other users who have an impact on additional time and expenses beyond the plan. If the delay comes from the contractor (Contractor), the contractor may be fined, as well as if the delay arises from the user of the service, the service user shall pay the loss incurred by the service provider, the amount stipulated in the contract in accordance with applicable legislation. Many studies have been done to determine the factors that cause the delay in completion of the project. Budgeted Cost of Work Scheduled (BCWS), describes the budget plan to a certain period of volume of the project plan to be done. Budgeted Cost of Work Performed (BCWP), describes the project plan budget for a certain period of what has been done on the actual volume of work. Land acquisition is the work of Kendari II railway project, at the time of execution of work there is a name of compensation made from the government to the community, if there is a community land whose land is affected by the project. The availability of budget is Kendari II road project, with length 38.15 km with budget amount Rp. 2.607.981.000,00 this is very limited. So that the contractor to carry out the project work according to the existing volume. Geographical conditions of the work of Kendari II city circle project, there are drawings of plans and work items before carrying out a project work. This research concludes that factors influencing the completion of construction project of Kendari II ring road.In accordance with the calculation of SPSS program (factor analysis) of 3 factors that affect the process of execution road construction project in Kendari City. The 3 factors that are contribution value in detail are: 1) availability of budget with value 93,3%, 2) land acquisition with value 68,5% and 3) Geographical condition with value 61,8%.